Experiencing and managing emotions in the workplace - Ashkanasy, Neal M. 1945-; Härtel, Charmine E. J. 1959-; Zerbe, W. J. (Emerald, 2012)
This volume contains a further selection of the best papers presented at the Seventh Emonet conference (Montreal, Canada, August 2010), following on from Volume 7 and augmented once again with invited chapters authored by leading scholars in the field. "Experiencing and managing emotions in the workplace" comprises fourteen chapters arranged in four sections: The experience of emotion; The dynamics of emotion; Regulating emotion; and The emotionally intelligent organization. These encompass a variety of methodological approaches, including qualitative and quantitative research, sourced from research conducted in organizations in the USA, Europe, and Australasia. The volume's secondary theme is "care and compassion", the theme of the Academy of Management meetings that followed the Emonet conference in Montreal. In effect, organizations that understand their members' emotions and utilize this information in their management practices become "emotionally intelligent" and capable of showing care and compassion to all stakeholders. The chapters in this book provide a rich and varied coverage of the latest developments in the study of the role of emotions in organizational settings.